Improvement of functional dyspepsia with Suaeda salsa (L.) Pall via regulating brain-gut peptide and gut microbiota structure. - Zhang, Wenjun; Wang, Xueyu; Yin, Shuanghui; Wang, Ye; Li, Yong; Ding, Yuling (European Journal of Nutrition, 2024)
Purpose: The traditional Chinese herbal medicine Suaeda salsa (L.) Pall (S. salsa) with a digesting food effect was taken as the research object, and its chemical composition and action mechanism were explored. Methods: The chemical constituents of S. salsa were isolated and purified by column chromatography, and their structures were characterized by nuclear magnetic resonance. The food accumulation model in mice was established, and the changes of the aqueous extract of S. salsa in gastric emptying and intestinal propulsion rate, colonic tissue lesions, serum brain-gut peptide hormone, colonic tissue protein expression, and gut microbiota structure were compared. Results: Ten compounds were isolated from S. salsa named as naringenin (1), hesperetin (2), baicalein (3), luteolin (4), isorhamnetin (5), taxifolin (6), isorhamnetin-3-O-β-d-glucoside (7), luteolin-3′-d-glucuronide (8), luteolin-7-O-β-d-glucuronide (9), and quercetin-3-O-β-d-glucuronide (10), respectively. The aqueous extract of S. salsa can improve the pathological changes of the mice colon and intestinal peristalsis by increasing the rate of gastric emptying and intestinal propulsion. By adjusting the levels of 5-HT, CCK, NT, SS, VIP, GT-17, CHE, MTL, and ghrelin, it can upregulate the levels of c-kit, SCF, and GHRL protein, and restore the imbalanced structure of gut microbiota, further achieve the purpose of treating the syndrome of indigestion. The effect is better with the increase of dose. Conclusion: S. salsa has a certain therapeutic effect on mice with the syndrome of indigestion. From the perspective of "brain-gut-gut microbiota", the mechanism of digestion and accumulation of S. salsa was discussed for the first time, which provided an experimental basis for further exploring the material basis of S. salsa.